2017
DOI: 10.1007/s00268-017-4058-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Extraesophageal Manifestations of Gastroesophageal Reflux Disease

Abstract: Extraesophageal manifestations of GERD are common, costly, and difficult to treat. ARS might be effective in highly selected patients, especially in those whose extraesophageal manifestations are caused by non-acid reflux. The available data to date are generally of poor quality or outdated. Well-designed randomized controlled trials or large-scale observational cohort studies are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 70 publications
0
19
0
4
Order By: Relevance
“…[95][96][97] A review of the surgical treatment for patients with chronic cough, LPR, and asthma found a surgical FP success rate between 48% and 94%. 98 The same group published a more recent review; according to a weighted mean per study per patient then compiled, 83.0% of patients (95% CI: 79.7-86.3%) experienced improvement, and 67.0% of patients (95% CI: 64.1-69.9%) experienced a resolution of symptoms. 99 It is noteworthy that the majority of the aforementioned studies of LPR identify a much lower success rate for FP than is seen in studies of GERD.…”
Section: Surgical Management In Lprmentioning
confidence: 99%
“…[95][96][97] A review of the surgical treatment for patients with chronic cough, LPR, and asthma found a surgical FP success rate between 48% and 94%. 98 The same group published a more recent review; according to a weighted mean per study per patient then compiled, 83.0% of patients (95% CI: 79.7-86.3%) experienced improvement, and 67.0% of patients (95% CI: 64.1-69.9%) experienced a resolution of symptoms. 99 It is noteworthy that the majority of the aforementioned studies of LPR identify a much lower success rate for FP than is seen in studies of GERD.…”
Section: Surgical Management In Lprmentioning
confidence: 99%
“…• GERL susijusi su didelio laipsnio diafragmos išvarža. Nepaisant chirurginio gydymo, daugeliui pacientų išlieka tolesnio ilgalaikio medikamentinio GERL gydymo poreikis [16].…”
Section: Gydymasunclassified
“…Для характеристики симптомов, возникающих выше пищевода, на уровне глотки и гортани, рядом авторов предложен термин «ларинго-фарингеальная рефлюксная болезнь» (laryngo-pharyngeal reflux disease -LPRD) [4]. Внепищеводные проявления ГЭРБ включают хронический кашель, заболевания гортани, бронхиальную астму (БА), пневмонию [5][6][7][8]. Астма и ГЭРБ очень часто связаны.…”
Section: ââåäåíèåunclassified